Effect of probiotic consumption on increasing the CD4+ T cell counts among Iranian patients living with HIV: A double-blind randomized clinical trial - Hamid Emadi-Koochak; Zeinab Siami; Jayran zebardast; SeyedAhmad SeyedAlinaghi; Ali Asadollahi-Amin (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - During the ART era, persistent immune activation remains a significant challenge in people living with HIV (PLWH). Microbial translocation play an essential role in this setting. Probiotics have several immunological benefits which can reverse this process. The purpose of this paper is to investigate the safety and efficacy of probiotics on CD4 counts among Iranian PLWH. Design/methodology/approach - In total, 50 PLWH with CD4 counts above 350 cells/mm3 did not receive ART participated in a randomized, double-blind trial and underwent 24 weeks of treatment with either LactoCare® or placebo twice daily. CD4 counts of the patients were measured at baseline, 12 weeks and 24 later in the two groups. Side effects were measured monthly using a specific checklist. Findings - The mean CD4 count of the patients showed a significant difference between the two groups after six months. Through six months follow up, the mean CD4 count of the patients showed a significant reduction as compared to the baseline in the placebo group; however, it did not show a significant difference in the probiotic group. Repeated Measures Anova test showed a significant effect for time × treatment interaction on the CD4 count during the trial course. No significant difference between the two groups concerning adverse events was reported. Originality/value - It seems the use of probiotics in PLWH with a CD4 count above 350 cells/mm3 who are not receiving antiretroviral drugs is safe and can reduce the devastating process of CD4+ T cells in these patients.